Ethical Life - KOHN, LIVIA (2026)
Traditional philosophy divides ethics into three major modes: utilitarianism (reward and punishment), deontology (the will of God), and virtue ethics (personal integrity). Daoists firmly support the latter, matching Martin Seligman’s understanding of key virtues and personality strengths. They also insist on ethics of difference and situation, noting that neither two people nor two cases are ever completely alike, thus necessitating adaptation and flexibility. Key virtues are accordingly tolerance and respect, coupled with a strong emphasis on the unique needs of the other person. Thus, the Golden Rule here is “do unto others as they would have us do unto them.” Another major dimension is the notion of freedom: from constraints, toward personal realization, and expressed in political liberty. Rulers should always listen and let go, never be controlling or tyrannical. The key personal relationship, moreover, is that of friendship, where like-minded people come together to join in peace and harmony, always accepting, always supporting, and without any major personal agendas.